Cuidado que el medicamento no se te salga por la nariz. - Feijoo Calles, Daniela; Moreno Royo, Lucrecia; Salar Ibáñez, Luis (Farmacéuticos Comunitarios, 2017)
Chronic obstructive pulmonary disease (COPD) is a pathology characterized by a persistent reduction in airflow. This lung disease is progressive and potentially life-threatening. It can cause shortness of breath and predisposes you to severe exacerbations and illness, and symptoms gradually worsen. A case of pharmacotherapeutic follow-up carried out in the Pharmaceutical Practice Classroom "Paco Martínez" of the Cardenal Herrera CEU University is presented to a real patient with COPD and polymedicated. It is used as a learning method based on problems. To support the evaluation of the situation, an analysis will be made of the different theories published on the ineffectiveness of treatment. In addition, the new approach to the treatment of COPD patients will be presented, assessing the heterogeneity of the disease and the clinical variability of each patient through bibliographic review in scientific databases PubMed/Medline and Google Scholar, in addition to searching for information on the different websites of official institutions, the World Health Organization and the Spanish Agency for Medicines and Health Products.